Digital Twins of Supply Chains: A Systems Approach - Jesus, Vitor; Kalaitzi, Dimitra; Batista, Luciano; Lopez, Nestor Leal (My University, 2024)
We tackle the problem of digitalization of supply chains, focusing on the collaboration and sharing of information. By generalizing the notion of digital twins, we review, develop, and conceptualize the (emerging) notion of digital twins of supply chains (DTofSC). While digital twins is an active research area with data available from numerous industry projects, its application to supply chains is just emerging as a cross discipline stemming from decades of maturing the notion of digital supply chains. While digital twins has been used in supply chains, the notion of digitalization of supply chains is only a nascent area, with imprecise definitions beyond key metaphors (e.g., visibility, traceability); as we conceptualize, the overall vision is to create technical and organizational mechanisms enabling any supply chain to be monitored and controlled from, e.g., a dashboard screen. After a literature review on the intersections between digital supply chains, digital twins, and digital technologies (e.g., blockchain), we propose a synthesis systems architecture of DTofSC, identify a key requirement gap (that we term addressability), and ground our contributions, and in the absence of real-world use-cases in practice, we apply our conceptualized systems architecture to battery recycling based on feedback from an industry-targeted workshop.